The impact of interest rate changes in the investment banking via the mechanism to attract deposits: nalytical study in Iraqi commercial banks (2004-2017 - علي احمد فارس; اسماء هادي نعمة (Iraqi Journal for Administrative Sciences, 2024)
The research aims to analyze the direction of bank deposits of all kinds as well as the nature of the changes in interest rates on these deposits and stand over the impact of these prices in the volume of deposits during the period of research, as well as to determine the reflection of interest rates on the nature of the investment banking by the volume of deposits affected by these prices. The research started from the problem of reluctance of owners of funds from the deposit in commercial banks and the preference of regional countries for reasons of security as well as the management of investments more efficiently than Iraqi banks, and this reluctance caused lack of availability of bank liquidity and then the performance of the bank and efficiency so it is necessary to find a mechanism to increase Bank deposits. Since interest rates on deposits are one of the tools to attract deposits globally, it is necessary to know the role of interest rates on deposits in stimulating the owners of funds on deposit and the extent of reflection in the nature of investment banking? The research a number of conclusions, the most important of which is that the interest rates on bank deposits (fixed and saving) are moving downward and continuously from 2007 to 2017. Moreover, Iraqi banks are more interested in cash credit than investing in financial assets due to the first of the bank's higher imports of interest Of the granting of loans or discount of commercial paper. The study recommended that banks' administrations seek to win depositors by granting acceptable benefits on fixed deposits and savings while easing the conditions imposed on depositors and urging them to put the largest amount in a bank deposit.